Extratemporal resections in pediatric epilepsy surgery—an overview. (April 2017) - Blount, Jeffrey P.
Summary: Despite optimized medical treatment, approximately one third of all patients with epilepsy continue to have seizures and by definition have medically resistant epilepsy (MRE). For these patients, surgical disruption of the epileptogenic network may enable freedom or great improvement in control of their seizures. The success of surgery is dependent on accurate localization of the epileptogenic zone and network. Epilepsy arising from regions of cortical dysplasia within the neocortex of the frontal, parietal, and occipital lobes show a propensity for reorganization and progressive decline in seizure freedom and consequent poorer surgical outcome. These procedures often require staged investigation with intracranial electrodes via subdural grids or stereoelectroencephalography (SEEG) and are considered extratemporal resections (ETRs). Central concepts include the following: (1) localization of epileptogenic and eloquent functional regions, (2) safe and effective placement of intracranial electrode arrays, (3) resection of epileptogenic cortex, and (4) avoidance of complications. Each of these concepts is summarized and developed in this summary paper.